2016
DOI: 10.3389/fpls.2016.00577
|View full text |Cite
|
Sign up to set email alerts
|

MYB Transcription Factors in Chinese Pear (Pyrus bretschneideri Rehd.): Genome-Wide Identification, Classification, and Expression Profiling during Fruit Development

Abstract: The MYB family is one of the largest families of transcription factors in plants. Although, some MYBs were reported to play roles in secondary metabolism, no comprehensive study of the MYB family in Chinese pear (Pyrus bretschneideri Rehd.) has been reported. In the present study, we performed genome-wide analysis of MYB genes in Chinese pear, designated as PbMYBs, including analyses of their phylogenic relationships, structures, chromosomal locations, promoter regions, GO annotations, and collinearity. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
128
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 132 publications
(143 citation statements)
references
References 56 publications
(87 reference statements)
15
128
0
Order By: Relevance
“…Therefore, we postulated that pear 4CL-related genes should occur at a certain degree of specific evolution to adapt to the environment during the process of differentiation from monocotyledonous plants. In the study of the MYB gene family, Cao et al found that the AtMYB genes in subfamily S12 may be a specific gene type to adapt to phytophagous conditions [55,56]. …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we postulated that pear 4CL-related genes should occur at a certain degree of specific evolution to adapt to the environment during the process of differentiation from monocotyledonous plants. In the study of the MYB gene family, Cao et al found that the AtMYB genes in subfamily S12 may be a specific gene type to adapt to phytophagous conditions [55,56]. …”
Section: Resultsmentioning
confidence: 99%
“…We found that 94 PbPRX genes contained different numbers of exons or introns, implying a great diversity in PRX gene family of pear. Many studies have shown that structural diversification of genes plays an important role in the evolution of multi-gene families (Muthamilarasan et al, 2014; Cao et al, 2016a,b,c; Han et al, 2016). In our research, we found that there presented different characteristics of PRXs from different subfamilies, indicating PbPRXs have functionally diversified.…”
Section: Discussionmentioning
confidence: 99%
“…Both events of tandem duplication and large-scale duplication are the main patterns of gene family expansion in plants, such as the MYB gene family in pear (Cao et al, 2016a), CHS gene family in maize (Han et al, 2016), or MYB gene family in Setaria italica (Muthamilarasan et al, 2014). In the present study, a high frequency of GRF genes was distributed in duplicated blocks, implying that large-scale duplications (whole-genome or segmental duplication) contributed to the expansion of the GRF gene family in plants.…”
Section: Discussionmentioning
confidence: 99%